The Similarities and Differences of “Say” and “Tell” (A Corpus Based Study) - Ika Handayani (English Department - Universitas Sultan Ageng Tirtayasa, 2022)
English foreign learners often have difficulty in distinguishing the collocation of the English words. The words produced may seem acceptable in terms of mean, yet it may not be common for native speakers of English. When one assumes that these words “tell” and “say” have similar in meaning, but in fact they have different in the use of context. The are several ways to find out the most appropriate collocations of various words one of them is by using corpora. This study used “English-Corpora.org (iWeb)”, “British National Corpus (BNC)”. This study is an attempt to explore the similarities and differences of two synonymous words by using English Corpora.org to find the collocation. The result shows the similarity is that both words have similar meanings and the concordance one. The similarity also seen in the findings of context. The word “say” is commonly found in the spoken context and fiction context. In the same context but different rate position, the word “tell” is commonly found in the fiction context and spoken activities. The differences are found in the collocation and the frequency rate